Reutilización de requisitos de usuario: el modelo mecano - Laguna, Miguel A.; García Peñalvo, Francisco José; López, Óscar (Revista Colombiana de Computación, 2002)
The requirements of an Information System come of very diverse formats. Their storage in a repository and the relationships between them and with another reusable elements could condition the success or failure of a reuse program. It is necessary to introduce a minimum degree of normalization in the requirements, so that they can be really reusable. Keywords: Requirement Engineering, requirement reuse, generic requirement, scenario, use case, Mecano model.